Optimalisasi Pascapanen Rumput Laut melalui Pelatihan Penggunaan Alat Pengering Energi Surya sebagai Strategi Penerapan Blue Economy di Wilayah Pesisir Desa Laikang Kabupaten Takalar - Amiruddin Amiruddin; Fiskia Rera Baharuddin; Mudarris Mudarris; Yustika Jauhari; Mukhlisin Mukhlisin (Jurusan Pendidikan Teknik Elektro, 2026)
The coastal community of Laikang Village, Takalar Regency, particularly the Pandala Berkah Seaweed Cultivators Group, faces serious challenges in the post-harvest stage. The conventional sun-drying method causes significant product quality degradation, especially during rainy seasons—with drying delays of up to 3–4 days causing discoloration, mold growth, and quality decline. As a result, selling prices of dried seaweed are only IDR 7,000–8,000/kg, far below the industrial market price of IDR 12,000–14,000/kg. This community service activity aims to optimize post-harvest processes through training on the use of a semi-enclosed solar energy dryer (solar dryer) as a blue economy implementation strategy in coastal areas. The implementation method includes socialization through Focus Group Discussion (FGD), technical and managerial training, participatory equipment assembly, and intensive field mentoring. The dryer with a capacity of 30–70 kg per cycle was designed with an indirect heating system based on polycarbonate materials, capable of achieving a stable temperature of 40–55°C without additional heat sources. Results show that 80% of participants understood hygienic drying techniques and temperature control, community participation reached 85%, and a local product identity